The Autophagy Inhibitor Spautin-1 Antagonizes Rescue of Mutant CFTR Through an Autophagy-Independent and USP13-Mediated Mechanism - Pesce, Emanuela; Sondo, Elvira; Ferrera, Loretta; Tomati, Valeria; Caci, Emanuela; Scudieri, Paolo; Musante, Ilaria; Renda, Mario; Baatallah, Nesrine; Servel, Nathalie; Hinzpeter, Alexandre; di Bernardo, Diego; et al. (Frontiers in Pharmacology, 2018)
The mutation F508del, responsible for a majority of cystic fibrosis cases, provokes the instability and misfolding of the CFTR chloride channel. Pharmacological recovery of F508del-CFTR may be obtained with small molecules called correctors. However, treatment with a single corrector in vivo and in vitro only leads to a partial rescue, a consequence of cell quality control systems that still detect F508del-CFTR as a defective protein causing its degradation. We tested the effect of spautin-1 on F508del-CFTR since it is an inhibitor of USP10 deubiquitinase and of autophagy, a target and a biological process that have been associated with cystic fibrosis and mutant CFTR. We found that short-term treatment of cells with spautin-1 downregulates the function and expression of F508del-CFTR despite the presence of corrector VX-809, a finding obtained in multiple cell models and assays. In contrast, spautin-1 was ineffective on wild type CFTR. Silencing and upregulation of USP13 (another target of spautin-1) but not of USP10, had opposite effects on F508del-CFTR expression/function. In contrast, modulation of autophagy with known activators or inhibitors did not affect F508del-CFTR. Our results identify spautin-1 as a novel chemical probe to investigate the molecular mechanisms that prevent full rescue of mutant CFTR.